Obesity is associated with impaired long-term prognosis in patients undergoing coronary angiography: results from a large-scaled single centre registry - Kuhn, Lasse; Akın, Ibrahim; Steinke, Philipp; Abumayyaleh, Mohammad S. A.; Ayoub, Mohamed; Mashayekhi, Kambis; Jannesari, Mahboubeh; Siegel, Fabian; Dürschmied, Daniel; Behnes, Michael; Schupp, Tobias (International journal of cardiology, 2025)
Background - The study investigates the prognostic value of body mass index (BMI) in a large cohort of unselected patients undergoing invasive coronary angiography (CA). More than one third of the world population is overweight or obese with increasing prevalence. Obesity is an established risk factor for the development of coronary artery disease (CAD), but its impact on outcomes in patients undergoing CA remains controversial. - Methods - Consecutive patients undergoing invasive CA were included at one institution from 2016 to 2022. Patients were stratified by BMI on admission according to the current WHO definition into the following subgroups: BMI 18.5- < 25 kg/m2, 25- < 30 kg/m2, 30- < 35 kg/m2 and ≥ 35 kg/m2. The prognostic value of BMI was investigated with regard to the primary endpoint rehospitalization for heart failure (HF) at 36 months and the secondary endpoints acute myocardial infarction (AMI) and coronary revascularization at 36 months. - Results - From 2016 to 2022, 6583 patients undergoing CA were included with a median BMI of 27.5 kg/m2 (mean: 28.3 kg/m2). Patients with a BMI of 25- < 30 kg/m2 had the highest prevalence of CAD (71.1 %) and 3-vessel CAD (30.5 %), whereas patients with a BMI ≥ 35 kg/m2 had the lowest prevalence (61.4 % and 20.1 %, respectively). After multivariable adjustment, patients with a BMI ≥ 35 kg/m2 had the highest risk of HF-related rehospitalization at 36 months compared to those with a BMI in the normal range (adjusted HR = 1.210; 95 % CI: 1.011-1.448; p = 0.038). - Conclusion - In patients undergoing CA, a BMI ≥35 kg/m2 was associated with the highest risk of HF-related rehospitalization at 36 months.